2017
DOI: 10.3221/igf-esis.42.02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of corrosion and sandblasting on the high cycle fatigue behavior of reinforcing B500C steel bars

Abstract: In a series of applications, steel reinforced concrete structures are subjected to fatigue loads during their service life, what in most cases happens in corrosive environments. Surface treatments have been proved to represent proper processes in order to improve both fatigue and corrosion resistances. In this work, the effect of corrosion and sandblasting on the high cycle fatigue behavior reinforcing steel bars is investigated. The investigated material is the reinforcing steel bar of technical class B500C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…overloading) aggressions of the environment, as well as by the capacity of the constituent materials to protect themselves against these aggressions. In this work, we are interested in the corrosion of reinforcement which is one of the main causes of degradation of reinforced concrete structures [2]. This corrosion induces a modification of the steel-concrete bond, a reduction in section of the steel bars, a decrease of the ductility of the steel as well as a peripheral damage of the concrete due to the pressure of the corrosion products.…”
Section: Introductionmentioning
confidence: 99%
“…overloading) aggressions of the environment, as well as by the capacity of the constituent materials to protect themselves against these aggressions. In this work, we are interested in the corrosion of reinforcement which is one of the main causes of degradation of reinforced concrete structures [2]. This corrosion induces a modification of the steel-concrete bond, a reduction in section of the steel bars, a decrease of the ductility of the steel as well as a peripheral damage of the concrete due to the pressure of the corrosion products.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, experimental observations demonstrated that severe corrosion impairs the fatigue accumulation and drop the useful life of a structure, especially at low strain amplitudes. In that sense, several studies have been conducted to investigate the coupled effect of dynamic loading along with the corrosive environment in RC structures [1,[10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%